Vitellogenesis in Bufo arenarum: Identification, characterization and immunolocalization of high molecular mass lipovitellin during oogenesis - O'brien Echeverría, Emma Dinorah (2010)
Vitellogenin (Vtg), a large lipoglycophosphoprotein, is the most important precursor of the yolk proteins, and the major source of nutrients for the developing embryo in oviparous species. After its uptake by the oocytes, Vtg is converted into lipovitellins (high and light) and phosvitin, which are deposited into crystalline yolk platelets. We describe here the presence of two high molecular mass lipovitellin isoforms in Bufo arenarum mature oocytes with masses of 113 and 100 kDa, respectively. The amino acid sequence analysis of p113 and p100 peptides showed a high sequence homology between both polypeptides and the complete reported sequences of Xenopus laevis vitellogenin. Using specific antibodies, we determined that the Vtg uptake begins early during oogenesis, at the previtellogenic stage, and continues until oocytes have reached their mature status. In addition, we found that large endocytic vesicles mediate Vtg uptake in stage I oocytes, and that the size of the endocytic vesicles declines with oogenesis progression. In terms of the Vtg protein trafficking, we detected the Vtg precursor (190 kDa) in the liver of estradiol-injected females. Finally, we propose a subclassification of B. arenarum stage II oocytes into three physiologically and morphologically distinct periods (early, mid and late).